The Effect of Regular Exercise Program on the Pain of the Elderly in Knee Osteoarthritis - Sara Safarnia shahri; Mohammad Reza Heidari; Meisam Moradi; Anoshirvan Kazemnejad (Iran University of Medical Sciences, 2022)
Background & Aims Knee osteoarthritis (KO) is one of the most common causes of pain, reduced function and disability in the elderly. Exercise is one of the methods suggested to manage the pain caused by KO. This study aims to determine the effectiveness of a home workout program on reducing  pain in the elderly with KO. Materials & Methods In this randomized controlled clinical trial conducted in March 2021 for three months, 70 older adults with KO were selected using a convenience sampling method and randomly assigned to exercise and control groups. The workout program was first implemented twice a day for 4 weeks in the clinic as a trial. Then, it was performed twice a day at home for another 4 weeks. Before and after the exercise, the patients were evaluated by the pain subscale of the Knee Injury and Osteoarthritis Outcome Score (KOOS). The collected data were analyzed in SPSS software, version 18 using independent t, paired t test, chi-square test, and Fisher's exact test. The significance level was set at 0.05. Results There was no statistically significant difference between the two groups in terms of demographic and clinical variables and in the mean pain score before the intervention (P=0.587). After the intervention, a significant reduction in pain intensity was reported in the exercise group (P= 0.009). Conclusion The home workout program is effective in reducing the pain of the elderly with KO. It is recommended to use it as a simple and cost-effective intervention to rehabilitate patients with KO along with other treatment methods.